Implementasi Aplikasi Keuangan Sederhana untuk Meningkatkan Efisiensi Laporan Keuangan - Desyanti, Desyanti; Suarlin, John; Yusrizal, Yusrizal (Journal of Social Responsibility Projects by Higher Education Forum, 2025)
In today's digital era, efficiency and accuracy in managing financial reports are important needs for every company. PT X, Dumai Branch, faces challenges in the financial recording process which is still done manually, making it prone to recording errors and delays in reporting. This community service aims to implement a simple financial application designed to simplify the process of recording transactions including employee data, salary data, ship expenditure data and preparation of financial reports. There are several stages carried out in this community service, namely problem identification, planning and design, socialization and training, implementation and testing, evaluation and monitoring. The results of the implementation show that this application is able to increase work efficiency, reduce the level of errors in recording, and accelerate the process of preparing financial reports. With a computerized system, PT X, Dumai Branch can manage its finances in a more structured and professional manner.